The Little Data Book 2011 - World Bank (World Bank, 2012)
The little data book 2011 is a pocket edition of world development indicators 2011. It is intended as a quick reference for users of the world development indicators database, book, and CD-ROM. The database, which covers more than 1,000 indicators and spans more than 50 years, is available at data. worldbank.org. The 213 country tables in the little data book present the latest available data for World Bank member countries and other economies with populations of more than 30,000. The 14 summary tables cover regional and income group aggregates.